Australians’ Financial Wellbeing and Household Debt: A Panel Analysis - Tahir, Muhammad S; Ahmed, Abdullahi D (My University, 2021)
“An excess of everything is bad”. This famous old proverb fits well with the current condition of Australian household debt that is continuously rising. Research in Australia’s household indebtedness is scarce and strategies to control the rising household debt remain contentious. The government of Australia has introduced financial literacy and financial capability measures to help control the rising household debt. Given that the literature highlights the importance of improving financial wellbeing, we analyse if financial wellbeing is a factor, which could be relevant to the reduced household debt. We use the Household, Income and Labour Dynamics in Australia panel survey in our analysis and find that improved financial wellbeing is associated with the reduced debt-taking behaviour of Australians. Our robust analysis confirms our findings. Finally, our empirical results suggest that improving households’ perception of their personal financial situation can bring improvement in their financial decisions, including the decision to take on debt.
Journal of Risk and Financial Management
Keywords: Income, wealth and finances